Natur Itself is a Physician - Usmanova Marjona Botirali (International Journal on Integrated Education, 2022)
The main purpose of writing this article is to look at nature's wonderful medicinal plants, medicinal and medicinal products, and their benefits for the human body. it is not difficult to get.